The psychology of willingness to pay: How self-expressive brand and fomo drive consumer behavior - Zulia Khairani; Nofrizal Nofrizal (Journal of Innovation in Business and Economics, 2025)
The purpose of this study is to prove that there are other factors that drive consumer behavior willing to pay for luxury smartphone products such as the iPhone series in developing countries, although in developed countries these products are commonplace. This study examines the role of self-expressive brand and FOMO in driving willingness to pay and the mediation of FOMO between self-expressive brand and willingness to pay for iPhone series which has never been tested before. The survey was conducted on 243 iPhone consumers. Data collection was done through google forms distributed on social media. Data analysis using the SmartPLS 3 software application was used to conduct structural equation modeling (SEM). The results showed that self-expressive brands and FOMO can encourage consumers to be willing to pay for iPhone series. In addition, FOMO can mediate a self-expressive brand with willingness to pay.